New water mite species (Acari, Hydrachnidia) from Vietnam - Tuzovskij, Petr V. (Zootaxa, 2013)
Descriptions of four new water mite species, Torrenticola vietnamica sp. nov. (female), Limnesia vietnamensis sp. nov. (female, deutonymph), Hygrobates gusakovi sp. nov. (male), Albaxona gusevi sp. nov. (female) from running waters of Vietnam are presented.